CRM index: an effective weapon for relationship enhancement. (1st January 2013) - Agariya, Arun Kumar; Singh, Deepali
A reliable and valid CRM (customer relationship management) index is developed in this paper. A standard methodology for scale development was followed; further to this the CRM index is developed through a case based method along with the customer and service provider weights. The findings clearly depict CRM as a multidimensional construct comprising factors namely claim payment security, knowledge about products, personalisation, transparency in product selling and service quality. A fair amount of literature on the Indian insurance sector dealt with identifying factors explaining the constructs of quality, value and satisfaction. But there is a paucity of research pertaining to industry-specific CRM index specifically catering to the Indian insurance sector. The proposed index will help in identifying issues that contribute to CRM and thereby formulating strategies accordingly, resulting in effective and efficient practices. The scores from organisational as well as customer's perspectives can be calculated so as to get newer insights.